ELECTRICAL CONDUCTIVITY PROPERTIES OF SOME THIAZOLYLAZOPYRIMIDINE DERIVATIVE COMPLEXES AT DIFFERENT T~MPERATURES (Biological Sciences - PJSIR, 2022)
The electrical conductivities of complexes of some thiazolylazo-pyrimidine derivative complexes have beeninvestigated at different temperatures. The complexes were found to be of two types; the first one has a semi-conductorbehaviour and a constant conductivity value above 398°K, whereas the second type shows three segments with variableactivation energy. The dissimilarity between the two types of complexes is attributed to the steric effect of the phenylgroup in the first type. The conductivity data measured in the temperature range 298° - 5700K were correlated to thegeometrical change of these complexes, indicating that the cobalt (II) complexes have higher conductivity than thoseof copper (1I) and nickel (II), depending on the chemistry of the metal ion and the molecular structure of complexes.Empirical equations to correlate ~E with log Go values for the complexes were deduced by the use of the least squaremethod. Also, the mobility values (m) of these complexes were calculated.